Risk factor analysis of nosocomial lower respiratory tract infection in influenza-related acute respiratory distress syndrome. (July 2020) - Chen, Wei-Chih; Kao, Kuo-Chin; Sheu, Chau-Chyun; Chan, Ming-Cheng; Chen, Yu-Mu; Chien, Ying-Chun; Peng, Chung-Kan; Liang, Shinn-Jye; Hu, Han-Chung; Tsai, Ming-Ju; Fang, Wen-Feng; Perng, Wann-Cherng; et al.
Background: Patients with severe influenza-related acute respiratory distress syndrome (ARDS) have high morbidity and mortality. Moreover, nosocomial lower respiratory tract infection (NLRTI) complicates their clinical management and possibly worsens their outcomes. This study aimed to explore the clinical features and impact of NLRTI in patients with severe influenza-related ARDS. Methods: This was an institutional review board approved, retrospective, observational study conducted in eight medical centers in Taiwan. From January 1 to March 31 in 2016, subjects were enrolled from intensive care units (ICUs) with virology-proven influenza pneumonia, while all of those patients with ARDS requiring invasive mechanical ventilation and without bacterial community-acquired pneumonia (CAP) were analyzed. Baseline characteristics, critical-illness data and clinical outcomes were recorded. Results: Among the 316 screened patients with severe influenza pneumonia, 250 with acute respiratory failure requiring intubation met the criteria of ARDS, without having bacterial CAP. Among them, 72 patients developed NLRTI. The independent risk factors for NLRTI included immunosuppressant use before influenza infection [odds ratio (OR), 5.669; 95% confidence interval (CI), 1.770–18.154], extracorporeal membrane oxygenation (ECMO) use after ARDS (OR, 2.440; 95% CI, 1.214–4.904) and larger corticosteroid dosage after ARDS (OR, 1.209; 95% CI, 1.038–1.407). Patients with NLRTI had higher in-hospital mortality and longer ICU stay, hospitalization and duration on mechanical ventilation. Conclusion: We found that immunosuppressant use before influenza infection, ECMO use, and larger steroid dosage after ARDS independently predict NLRTI in influenza-related ARDS. Moreover, NLRTI results in poorer outcomes in patients with severe influenza. The reviews of this paper are available via the supplemental material section.